Environmental disclosure in corporate websites: a study in Brazil and USA companies - Anastácia Rosa Portella; José Alonso Borba (RAUSP Management Journal, 2020)
Purpose – The internet allows much corporate information to be instantly accessed from anywhere, at any time. To better inform the more diverse stakeholders, companies have used their websites as another tool for disclosure. The purpose of this paper is to contribute to the area of environmental accounting, as it investigates whether the companies located in different countries, from different sectors, in different stages of development and regulatory environments present different levels of environmental disclosure and to explain the environmental disclosure extension on corporate websites of companies in Brazil and the USA through corporate characteristics. Design/methodology/approach – To achieve such purpose, an environmental disclosure index (EDI) was created and a model was used to investigate whether the variables environmental performance, size, profitability, debt, sector and country explain the disclosure on the website. Findings – It was pointed that US companies stood out compared to Brazilian companies throughout the EDI. On the one hand, the statistical model suggests that the variables, namely, organization size, sector and country of origin of the company, explain the environmental disclosure in corporate website, whereas the profitability and debt variables were not significant in the model. On the other hand, the environmental performance variable proved to be significant; however, it was contrary to what was expected from the theory of legitimacy, once a negative relation between environmental disclosure and environmental performance is expected. Originality/value – It is considered that transnational studies on corporate environmental responsibility can improve the understanding and eventually explain the difference of this disclosure.